Applications of Burzynski failure criteria. Part I. Isotropic materials with asymmetry of elastic range - FRĄŚ, T.; KOWALEWSKI, Z. L.; PĘCHERSKI, R. B.; RUSINEK, A. (Engineering Transactions, 2014)
The main idea of energy-based hypothesis of material effort proposed by Burzynski is briefly presented and the resulting failure criteria are discussed. Some examples, based on the own studies, which depict applications of these criteria are discussed and visualizations of limit surfaces in the space of principal stresses are presented.